Étude de l'effet de la convergence des parois axiales sur la rétention des couronnes scellées - Pamela BEJJANY; Nouhad RIZK (International Arab Journal of Dentistry (IAJD), 2012)
The aim of this in vitro study is to investigate the variation in the retention of ceramo-metallic crowns on identical dental preparations, differing only by the convergence of their axial walls. Materials and methods: Sixty molars were prepared; the convergence of the axial walls was of 20 degrees (maximum convergence), 30 degrees (acceptable convergence) or 60 degrees (critical convergence putting at risk the durability of treatment). Infrastructures were sealed using two types of ciment- a resin and a glass ionomer ciments- for the same axial convergence. Results: for small angulations (<30 degrees), the use of glass ionomer ciment provided a higher retention than that provided by the resin ciment. For conical dental preparations (≥30 degrees), bonding with resin ciment offered a better retention and a greater resistance to displacement forces.